0.05–3 GHz VNA characterization of soil dielectric properties based on the multiline TRL calibration. (12th January 2017) - Lewandowski, Arkadiusz; Szypłowska, Agnieszka; Kafarski, Marcin; Wilczek, Andrzej; Barmuta, Paweł; Skierucha, Wojciech
Abstract: We present a methodology for characterization of soil relative dielectric permittivity in the frequency range 0.05–3 GHz. Soil samples are placed in a measurement cell constructed out of a EIA 1 - 5 / 8 " coaxial transmission line, and then measured with a calibrated vector-network-analyzer. From these measurements the relative dielectric permittivity is obtained by use of a modified Boughriet algorithm. In order to calibrate the vector-network-analyzer directly at the EIA 1 - 5 / 8 " coaxial-transmission-line measurement planes, we use the multiline through-reflect-line method. This method, while providing superior vector-network-analyzer calibration accuracy, is also easy to implement since it uses only transmission lines with known lengths and a single unknown highly-reflective termination. The implemented calibration method was compared to a simplified approach that uses the standard SOLT calibration in Type-N reference planes, and then accounts for the Type-N/EIA 1 - 5 / 8 " adapters by removing their electrical delay. Experimental results for teflon and soil samples with different moisture content and salinity confirmed the validity of our approach.